Optimization of the Extraction Conditions of Antioxidant Phenolic Compounds from Strawberry Fruits (Fragaria x ananassa Duch.) Using Response Surface Methodology - Koraqi, Hyrije; Petkoska, Anka Trajkovska; Khalid, Waseem; Sehrish, Aqeela; Ambreen, Saadia; Lorenzo, Jose Manuel (Food analytical methods, 2023)
The subject of this study is to determine the best solvent and optimum extraction conditions for the extraction of maximum antioxidant phenolic compounds and antioxidant activity from strawberry fruits ( Fragaria x ananassa Duch .). Extractions were carried out using solvents with different polarities (water, methanol, ethanol, acetonitrile, and acetone). Box-Behnken Design was used to optimize extraction conditions, including extraction time (t), temperature (°C), and liquid/solid (L/S) ratio. In the study, extracts obtained with acetone indicated the highest total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity. The optimal extraction conditions for both responses were determined to be time of 17.5 min, temperature 52.5 °C, and liquid/solid ratio of 30:1. The maximum TPC and TFC values were found as 18.78 ± 0.22 mg of gallic acid equivalent (GAE/g) and 10.52 ± 0.35 mg of catechin equivalents (CE/g) under optimum extraction conditions. The results indicated that optimizing extraction conditions is critical for quantifying antioxidant phenolic compounds. The present model can contribute to finding a cheap way of delivering natural antioxidants in the food, cosmeceutical, and pharmaceutical industries. Furthermore, these results indicate that strawberry fruits ( Fragaria x ananassa Duch .) can be a natural food colorant in dietary applications with potential health benefits.